Properties of Western Cape concrete with metakaolin - Bakera, Alice Titus (Department of Civil Engineering, 2019)
More than four billion of tons of cement are produced annually for construction purposes in the world. This is associated with high production costs and environmental pollution, since cement manufacturing requires fuel to run the processes, and emits carbon dioxide (CO2) during the burning of raw materials. With these problems, the use of Supplementary Cementitious Materials (SCMs) is found to be an appropriate solution, as it contributes to the reduction of cement used in concrete by partially replacing cement with SCMs. However, a challenge arises as to the availability of SCMs. This is mainly because many SCMs such as slag, fly ash, and silica fume are industrial by-products. This means that any fluctuation in the production of the primary products (steel, electrical power, and silicon metal) directly affects their availability. Therefore, an alternative SCM such as metakaolin, which is obtained from calcination of kaolin clay, is a potential solution to SCM availability fluctuation, especially in the Western Cape construction industry which depends on the use of Corex slag (GGCS) from a source that can be variable. This raises the need to investigate the properties of concrete with metakaolin, in order to assess its potential for use as an alternative SCM in the Western Cape. The properties of concrete with a locally available metakaolin were studied with the following specific objectives; i) to characterize metakaolin in terms of its morphology and pozzolanic activity, ii) to assess the influence of metakaolin on fresh and hardened concrete properties, and to compare these with the properties of concrete with GGCS, iii) to assess the influence of metakaolin on the deformation behaviour of concrete, iv) to evaluate the durability properties of concrete containing metakaolin by assessing its potential to mitigate Alkali Silica Reaction (ASR), and to reduce concrete penetrability. The study followed two methodologies; a substantial and critical literature review of the use of metakaolin in concrete, and laboratory investigations on the performance of metakaolin in mortar and concrete. In the literature review, metakaolin was shown to enhance the properties of concrete. However, various contradictions were highlighted on the influence of metakaolin on certain properties of concrete, such as setting times and tensile splitting strength. Moreover, there were limited studies on the deformation behaviour (especially creep) of concrete with metakaolin, as well as the potential of metakaolin to mitigate ASR. Besides, the characterization of Western Cape concrete with metakaolin had not been extensively studied. Therefore, these gaps raised a need for experimental investigations. The experimental investigations involved six categories; i) Morphology of metakaolin using Scanning Electron Microscopy (SEM) analysis, ii) pozzolanic reactivity using three tests; strength activity index test, heat of hydration test (semi-adiabatic and isothermal calorimetry tests), and thermogravimetric analysis (TGA), iii) fresh properties of concrete assessed by setting time and workability, iv) hardened properties of concrete using compressive strength, tensile splitting strength, and porosity using Mercury Intrusion Porosimetry (MIP), v) deformation behaviour of concrete using static elastic modulus, and creep and shrinkage tests, and finally, vi) durability properties of concretes assessed by Durability Index (DI) tests, accelerated mortar bar test (ASR), accelerated carbonation test, and chloride bulk diffusion test. Special mortars were designed for pozzolanic activity and accelerated mortar bar tests, while three groups of concretes i.e. with 0.4, 0.5, and 0.6 water/binder (w/b) ratios with five different replacement rates of SCMs (0%, 10%, 15%, and 20% metakaolin, and 50% GGCS) were designed and cast for hardened properties and durability tests. Experimental results showed that metakaolin had a significant influence on Western Cape concrete properties. It was found that metakaolin had a high pozzolanic activity. Metakaolin in concrete was found to increase setting times while decreasing workability. Compressive and tensile splitting strengths were enhanced by metakaolin, with the highest strengths at 20% replacement level with an increase of approximately 47% and 41% in comparison with the controls, respectively. Metakaolin was found to have a greater influence on concrete with higher w/b ratio. Metakaolin was also found to alter the microstructure of concrete by refining the pores and minimizing their connectivity. The deformation behaviour was also affected by metakaolin. It was found that metakaolin increased the elastic modulus of concrete while decreasing creep and drying shrinkage of concrete. With increasing metakaolin content, the durability of concrete in terms of transport properties, and resistance against deleterious chemical processes was improved. It was concluded that the addition of metakaolin helped to produce concrete with excellent quality. In comparison to GGCS, it was found that in most of the investigated concrete properties, metakaolin outperformed GGCS at equivalent mix proportions. Technically, metakaolin can therefore be used as a substitute for GGCS in concrete in the Western Cape, thereby contributing a solution to the potential scarcity of SCMs, and potentially reducing environmental effects. Nevertheless, challenges remain on the cost effectiveness, and the willingness and awareness of the construction industry in adapting its use.